Maternal cardiac myxoma during pregnancy - Reyna-Villasmil, Eduardo (2017)
Atrial myxomas may cause serious disability in pregnant women. Clinical features depend on location, size and mobility. Embolism, intracardiac obstruction and constitutional symptoms may be the initial presentation. Surgical excision is the definitive treatment. Only twenty cases have been previously published. We report a case of a cardiac myxoma in a pregnant patient who attended the cardiology service at 29 weeks of gestation where the echocardiogram revealed a mass in the left atrium. Elective caesarean section was performed at 34 weeks. Five days later, cardiopulmonary bypass surgery and excision of myxoma five days later. This potentially life-threatening condition highlights the importance of considering of rare medical problems presenting during pregnancy.